On the Assocıated Curves of a Frenet Curve in ???? ?? - Çetin, Esra Çiçek; Bektaş, Mehmet; Yılmaz, Münevver Yıldırım (My University, 2022)
In the present work, we have dealt with the properties of associated curves of a Frenet curve in ???? ??. In addition to this, we define principal direction curve, ???? ?direction curve, ???? ? direction curve of a given Frenet curve by using integral curves of 4-dimensional Minkowski space. Then we introduce some characterizations for general helix and slant helix. Finally, some new associated curves and theorems obtained for space-like curves and time- like curves in ???? ??. Also, an example is given.
Keywords: Matematik